2017
DOI: 10.3389/fsurg.2017.00044
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Recurrence Rate and De Novo Incontinence after Endoscopic Treatment of Vesicourethral Stenosis and Bladder Neck Stenosis

Abstract: ObjectivesThe objective of this study was to compare the recurrence rate and de novo incontinence after endoscopic treatment of vesicourethral stenosis (VUS) after radical prostatectomy (RP) and for bladder neck stenosis (BNS) after transurethral resection of the prostate (TURP).MethodsRetrospective analysis of patients treated endoscopically for VUS after RP or for BNS after TURP at three German tertiary care centers between March 2009 and June 2016. Investigated endpoints were recurrence rate and de novo inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Recently, robot-assisted laparoscopic subtrigonal inlay of buccal mucosa for recurrent BNC was reported [15]. In our algorithm, open reconstruction is performed latest after three attempts of endoscopic treatment, as Kranz et al [8] showed a significantly lower success rate for endoscopic treatments if performed more often.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, robot-assisted laparoscopic subtrigonal inlay of buccal mucosa for recurrent BNC was reported [15]. In our algorithm, open reconstruction is performed latest after three attempts of endoscopic treatment, as Kranz et al [8] showed a significantly lower success rate for endoscopic treatments if performed more often.…”
Section: Discussionmentioning
confidence: 99%
“…While some risk factors for the development of BNC have been established or proposed, apparently, little can be done to safely avoid them. Established risk factors are small prostatic size at surgery [8,9], untreated prostatitis at time of surgery, long resection time, and extensive resection at the bladder outlet [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success rates after primary incision or resection range between 37 and 69%. This rate may increase up to 91% after numerous sequential surgical procedures (8,10,32). There are only two publications to exclusively report on endoscopic treatment of VUAS and most of the published series do not distinguish between a BNC after surgery for benign prostatic hyperplasia and VUAS after RP.…”
Section: Treatment Endoscopic Proceduresmentioning
confidence: 99%
“…Moreover, it seems inevitable to us to distinguish between a bladder neck contracture (BNC) after surgical procedures for benign prostatic hyperplasia and VUAS after RP (7). It is a known fact, that etiology, anatomy, recurrence rates, and functional outcomes differ significantly between BNC and VUAS (8). BOO after PCa treatment includes radiation-induced bulbomembranous urethral stricture (9) as well as VUAS after RP (10).…”
Section: Introductionmentioning
confidence: 99%